Germination characteristics and intrapopulation variation in carob (Ceratonia siliqua L.) seeds - Pérez-García, F. (Spanish Journal of Agricultural Research, 2009)
The aims of this work were to study the germination characteristics (under controlled conditions of light and temperature and using different pretreatments for promoting germination) and variability of Ceratonia siliqua seeds. Seed collected from different individual trees were tested. Constant (10 deg C, 15 deg C, 20 deg C, 25 deg C) and alternating 25/15 deg C temperature regimes and 16/8 h light/dark photoperiod conditions were used. Mechanical scarification, dry heat, boiling water, sulphuric acid, soaking in distilled water and soaking in gibberellic acid solution were used as presowing treatments applied for enhancing germination. The untreated seeds showed a deep dormancy at all temperature regimes assayed (final germination percentages ranged from 23 to 28%). Mechanical scarification, sulphuric acid and boiling water drastically improved final germination percentages (99, 88 and 80%, respectively). Therefore, the impermeability to water of the seed coat (physical dormancy) seems to be the most important causes of the seed dormancy present in this species. Great variability in seed weight, seed water content and germination parameters were found among seeds belonging to different individual trees. Significant differences between different individual trees under the same incubation temperature were detected for seed germination (final germination percentage ranged from 7 to 50%). However, germination rate (as expressed by mean germination time) was relatively similar among seeds from different trees. A negative significant relationship between seed weight and final germination percentage was found: the lightest seeds reached the highest germination percentages. Moreover, seed weight showed a positive significant correlation with seed water content.